Monte Carlo study of the depth‐dependent fluence perturbation in parallel‐plate ionization chambers in electron beams. Issue 11 (14th October 2014) - Zink, K.; Czarnecki, D.; Looe, H. K.; von Voigts‐Rhetz, P.; Harder, D.
Abstract : Purpose: The electron fluence inside a parallel‐plate ionization chamber positioned in a water phantom and exposed to a clinical electron beam deviates from the unperturbed fluence in water in absence of the chamber. One reason for the fluence perturbation is the well‐known "inscattering effect, " whose physical cause is the lack of electron scattering in the gas‐filled cavity. Correction factors determined to correct for this effect have long been recommended. However, more recent Monte Carlo calculations have led to some doubt about the range of validity of these corrections. Therefore, the aim of the present study is to reanalyze the development of the fluence perturbation with depth and to review the function of the guard rings. Methods: Spatially resolved Monte Carlo simulations of the dose profiles within gas‐filled cavities with various radii in clinical electron beams have been performed in order to determine the radial variation of the fluence perturbation in a coin‐shaped cavity, to study the influences of the radius of the collecting electrode and of the width of the guard ring upon the indicated value of the ionization chamber formed by the cavity, and to investigate the development of the perturbation as a function of the depth in an electron‐irradiated phantom. The simulations were performed for a primary electron energy of 6 MeV. Results: The Monte Carlo simulations clearly demonstrated a surprisingly large in‐ and outward electron transport across the lateral cavity boundary. This results in a strong influence of the depth‐dependent development of the electron field in the surrounding medium upon the chamber reading. In the buildup region of the depth‐dose curve, the in–out balance of the electron fluence is positive and shows the well‐known dose oscillation near the cavity/water boundary. At the depth of the dose maximum the in–out balance is equilibrated, and in the falling part of the depth‐dose curve it is negative, as shown here the first time. The influences of both the collecting electrode radius and the width of the guard ring are reflecting the deep radial penetration of the electron transport processes into the gas‐filled cavities and the need for appropriate corrections of the chamber reading. New values for these corrections have been established in two forms, one converting the indicated value into the absorbed dose to water in the front plane of the chamber, the other converting it into the absorbed dose to water at the depth of the effective point of measurement of the chamber. In the Appendix, the in–out imbalance of electron transport across the lateral cavity boundary is demonstrated in the approximation of classical small‐angle multiple scattering theory. Conclusions: The in–out electron transport imbalance at the lateral boundaries of parallel‐plate chambers in electron beams has been studied with Monte Carlo simulation over a range of depth in water, and new correction factors, covering all depths and implementing the effective point of measurement concept, have been developed.